Going Green Is Exhausting for Dark Personalities but Beneficial for the Light Ones: An Experience Sampling Study That Examines the Subjectivity of Pro-environmental Behavior - Kesenheimer, Jana Sophie; Greitemeyer, Tobias (Frontiers in Psychology, 2022)
Study 1 examined how personality and attitudes are related to daily pro-environmental behavior (PEB) and whether these relationships are moderated by perceived behavioral costs and benefits. One-hundred-and-seventy-eight participants responded to scales measuring the dark and light side of personality, as well as their pro-environmental attitude. Afterward, they were notified three times a day for seven days in a row. Each time they reported their PEB that had occurred in the past four hours and indicated their behavioral costs and benefits. Multilevel analyses showed a positive relationship between the frequency of PEB and the light triad of personality and pro-environmental attitude, while the dark tetrad was negatively related to PEB. Unexpectedly, less environmentally aware participants reported to engage in PEB with higher costs and lower benefits than did pro-environmental participants. A second study (N = 159) suggests that less environmentally aware people do not actually engage in PEB with high costs and low benefits, but rather that they only perceive their behavior to be costly and of little benefit. Overall, our findings suggest that the way people perceive their daily PEB is not necessarily shared by others.